2017
DOI: 10.1016/j.arth.2017.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Cryotherapy With Dynamic Intermittent Compression Improves Recovery From Revision Total Knee Arthroplasty

Abstract: This is the first report dealing with the use of CDIC after rTKA. According to our results, it improves the recovery of patients who underwent rTKA; thus, it should be integrated into our daily practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The best results associated with CWI application can be explained by the greater cooling area of contact [7], the hydrostatic pressure that redirected the skin blood flow to the central circulation [27], and the local vasoconstriction that reduces the fluid flux into the interstitial space. The intervention with CGRC provided satisfactory results that may be related to cooling associated with compression [12]. The results achieved for the effects of cryotherapy on agility performance, evaluated by SHT, confirmed the findings of previous studies, such as those reported by Macedo, et al [22] and Furmanek, Słomka, & Juras [28] who showed worse functional performance immediately after CWI application.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The best results associated with CWI application can be explained by the greater cooling area of contact [7], the hydrostatic pressure that redirected the skin blood flow to the central circulation [27], and the local vasoconstriction that reduces the fluid flux into the interstitial space. The intervention with CGRC provided satisfactory results that may be related to cooling associated with compression [12]. The results achieved for the effects of cryotherapy on agility performance, evaluated by SHT, confirmed the findings of previous studies, such as those reported by Macedo, et al [22] and Furmanek, Słomka, & Juras [28] who showed worse functional performance immediately after CWI application.…”
Section: Discussionsupporting
confidence: 84%
“…Among the cryotherapy techniques the ice pack is a low-cost device which is easily accessible, causing a reduction in tissue temperature and physiological changes to at least one centimeter [5,6], the cold water immersion (CWI) allows a greater body area to be exposed to cold [7], maintaining tissue cooling for longer and providing increased analgesia [8] and cryotherapy with intermittent compression can deliver similar results [9,10]. The literature shows that cryotherapy with intermittent compression is widely used for recovery of ligament injuries [11], total knee arthroplasty [12] and reduction in post-operative pain [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…became popular after receiving patents in the 1990s and early 2000s. Initially implemented for recovery following surgical procedures, such as knee arthroplasty (Su et al 2012 ; Murgier et al 2017 ; Schinsky et al 2016 ), knee arthroscopy (Waterman et al 2012 ; Murgier and Cassard 2014 ), hip arthroplasty (Leegwater et al 2012 ), hip arthroscopy (Klaber et al 2019 ), and spine surgery (Nabıyev et al 2018 ; Bellon et al 2019 ), these devices deliver continuous or intermittent compression whilst simultaneously supplying low temperature “exchange fluid” to the injured area. Importantly, they can be applied for as long a time period as desired without substantial change in the temperature of the material contacting the affected area.…”
Section: The Changing Face Of Cryotherapymentioning
confidence: 99%
“…DC therapy is a combination of continuous flow cryo-therapy and intermittent compression. It is an up-to-date analgesic regimen in extremity surgery and its efficiency has been demonstrated after anterior cruciate ligament reconstructions and revision surgeries of total knee arthroplasties [6,13].…”
Section: Discussionmentioning
confidence: 99%